Sujeitos diaspóricos e negociações identitárias: o entre-lugar em Brazil-Maru e Sonhos Bloqueados - Otenio, Marta Matsue Yamamoto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this contemporary world it is strongly discussed the issue of plural identities, hyphenated individuals, mestizos, which stimulates the individuals to the ceaseless search for identity construction. The transition from a feudal era into modernization forced thousands of Japanese to search for better conditions of life in overseas lands. In the context of Japanese Diaspora to Brazil, we intend to analyze the traces of cultural hybridity in the way of life of these immigrants represented in literature. At first, we can note a certain resistance to assimilation of the Brazilian culture, as well as an aversion to the other culture. However, on the assumption that a cultural hybridization process is inevitable to identities construction in diasporic conditions, these immigrants had to negotiate the inclusion of Brazilian customs in their cultural traditions. In this sense, the present work has the main purpose to point the main cultural hybridizations acquired by these immigrants and Japanese descendants. Thereby, the in-between seems to be a welcome space that enables the review of principles of crystallized structure units and then, to allow a plasticity in the identity negotiation of this diasporic individual. Therefore, the research has as main focus the novels Sonhos bloqueados, by Japanese-Brazilian Laura Honda-Hasegawa and Brazil-Maru, by Japanese- American Karen Tei Yamashita. Honda-Hasegawa and Yamashita are two Japanese descendant writers that give voice to their female characters and stimulate us to discuss how the identities are complex in post-modernity, breaking with the idea of centralized and fixed identity. Moreover, even if Karen Tei Yamashita and Laura Honda-Hasegawa are innovators, both still remain conservatives

No mundo contemporâneo fala-se insistentemente em identidades plurais, sujeitos hifenizados, mestiços, o que impulsiona o sujeito à busca incessante da construção identitária. A transição de uma era feudal para a modernização obrigou milhares de japoneses a buscarem melhores condições de vida em terras ultramarinas. No contexto da diáspora japonesa para o Brasil, pretendemos analisar os vestígios de hibridismo cultural no modo de viver desses imigrantes representados pela literatura. No início, podemos perceber uma certa resistência à assimilação da cultura brasileira, bem como a aversão à cultura do outro. Contudo, partindo do pressuposto de o processo de hibridação cultural ser inevitável à construção de identidades em condições diásporicas, esses imigrantes tiveram que negociar a inclusão de costumes brasileiros em suas tradições culturais. Nesse sentido, o presente trabalho tem como objetivo principal apontar as principais hibridações culturais sofridas por esses imigrantes e descendentes de japoneses. Desse modo, o entre-lugar parece ser um espaço acolhedor que possibilita a revisão dos princípios de estruturas cristalizadas de unidades e, assim, permitir uma plasticidade na negociação identitária desse sujeito diaspórico. Para tanto, a pesquisa tem como foco principal os romances Sonhos bloqueados, da nipo-brasileira Laura Honda-Hasegawa e Brazil-Maru, da nipo-estadunidense Karen Tei Yamashita. Honda-Hasegawa e Yamashita são duas escritoras descendentes de japoneses que dão voz às suas personagens femininas, e nos incitam ao debate de como as identidades na pós-modernidade são complexas, rompendo com a ideia de uma identidade fixa e centralizada. Ademais, Karen Tei Yamashita e Laura Honda-Hasegawa por mais inovadoras que sejam, elas ainda se mantêm conservadoras
Keywords: Japoneses - Brasil; Nipo-brasileiros; Japanese; Japão - Migração